Thermodynamic Uncertainty Relations in Driven Open Quantum Systems: Bounds on Precision and Dissipation Beyond the Markovian Approximation - Pereira, Sofia; Lopes, Carlos; Carvalho, Marta (Journal of Tecnologia Quantica, 2026)
Thermodynamic Uncertainty Relations in Driven Open Quantum Systems: Bounds on Precision and Dissipation Beyond the Markovian Approximation